3D face candidate region detection using background subtraction / Zulfikri Paidi and Nurzaid Muhd Zain - Paidi, Zulfikri; Muhd Zain, Nurzaid (UiTM Cawangan Perlis, 2016)
In this paper, we have explored 3D face candidate region detection using background subtraction. Our focus is to solve the first challenge in face registration, which is to detect and identify face region. From the experiment, it shows some promising results related to using background subtraction in face candidate region detection algorithm. Firstly, we have succeeded in generating an oval shape for boundary region detection. Secondly, our face candidate region detection rate in percentage using background subtraction is 72.5% higher compared when background subtraction is excluded, which achieved only 60% of success rate.